2018
DOI: 10.1186/s12868-018-0426-z
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear morphology in the developing inner ear of the porcine model of spontaneous deafness

Abstract: BackgroundAuditory function and cochlear morphology have previously been described in a porcine model with spontaneous WS2-like phenotype. In the present study, cochlear histopathology was further investigated in the inner ear of the developing spontaneous deafness pig.ResultsWe found that the stria vascularis transformed into a complex tri-laminar tissue at embryonic 85 days (E85) in normal pigs, but not in the MITF−/− pigs. As the neural crest (NC) of cochlea was derived by melanocytes. MITF mutation caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It is known from canine histologic studies that deaf cochleae have a degenerated stria, but the cause and mechanism of degeneration are not known. Melanocyte precursors migrate in the embryo from the neural crest to the cochlea where they develop from melanoblasts into functional melanocytes, a process involving multiple transcription factors and other signaling molecules [26,27,28]. Recent studies of a naturally occurring pigment-associated deafness disorder in Rongchang pigs caused by a de novo silencer mutation in MITF-M expression [15] documented the embryonic and postnatal development of the stria [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from canine histologic studies that deaf cochleae have a degenerated stria, but the cause and mechanism of degeneration are not known. Melanocyte precursors migrate in the embryo from the neural crest to the cochlea where they develop from melanoblasts into functional melanocytes, a process involving multiple transcription factors and other signaling molecules [26,27,28]. Recent studies of a naturally occurring pigment-associated deafness disorder in Rongchang pigs caused by a de novo silencer mutation in MITF-M expression [15] documented the embryonic and postnatal development of the stria [28].…”
Section: Introductionmentioning
confidence: 99%
“…Melanocyte precursors migrate in the embryo from the neural crest to the cochlea where they develop from melanoblasts into functional melanocytes, a process involving multiple transcription factors and other signaling molecules [26,27,28]. Recent studies of a naturally occurring pigment-associated deafness disorder in Rongchang pigs caused by a de novo silencer mutation in MITF-M expression [15] documented the embryonic and postnatal development of the stria [28]. They showed that a normal stria vascularis did not develop in MITF -/pigs, normally present in embryonic day 85 (E85) pigs, but instead consisted of a thin, loose collection of cells that included intermediate cells in affected pigs, followed by collapse of the cochlear duct by E100, followed by degeneration of spiral ganglion neurons by postnatal day 30.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological features of the organ of Corti have already been measured in the hemicochlea preparation [37,41,42,43]; however, the phalangeal processes of the Deiters’ cells are largely covered by the OHCs and the development of this subcellular compartment could not be explored. Biophysical studies and modelling supposed that the phalangeal processes have important roles in the cochlear micromechanics [32,44], thus we investigated the structural development of Deiters’ cells’ subcellular compartments in two different cochlear turns while using the hemicochlea preparation combined with single-cell electroporation dye-loading [30].…”
Section: Discussionmentioning
confidence: 99%
“…In all measured developmental stages, processes in the apical turn were longer, in correlation with the tonotopic rule. Phalangeal processes of the Deiters’ cells typically form tight junctions with the apical end of OHCs located one to three cells in the apical direction and in the adjacent lateral row [44,45]. This means that the length of the processes and nearby OHCs correlates.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were dehydrated through 95% alcohol and absolute alcohol and cleared in xylene twice, 5 min for each time. Finally, the mounted sections were observed under a light microscope [23].…”
Section: Real-time Quantitative Pcrmentioning
confidence: 99%